(untitled) (GIST – Education and Learning Research Journal, 2018)
The prominence of technology has always been booming since computers generated new lanes for human to make use of high-tech for many different purposes. Utilizing computers for learning goals, among many, is one of the main concerns followed by educational issues in teaching and learning, especially, of a new language. Computer-assisted language learning (CALL) is known as a branch of language studies which focuses on teaching and learning of a new language through applications of computers in language learning contexts. Many books, articles, reviews, and etc. being published regularly consider one or some issues related to the CALL. To this, researchers have tried to introduce or evaluate particular application of CALL in the mentioned field. Cameron (1988, p. 15) reasons that “The fact that there are so many different types of CALL programs in existence illustrates the futility of attempting to define a single set of program principles or structures to fit all situations.” Other subordinate technologies interconnected to the computerized exemplar have arrived the inclined in practice. For example, information communication technology (ICT) “has been integrated within the overall design of the methodology used in the language learning process is a key factor.” (Zhang, 2012, p. 8). Other similar well-intentioned works can be referred to as (Holland & Fisher, 2008; Donaldson & Haggstrom, 2006; Thomas, Reinders, & Warschauer, 2013) which consider discussions of series of actions taken as regards the CALL subject. Beatty’s “teaching and research in computer-assisted language learning” (2010) is considered as one of the most comprehensive books on defining and reorganizing concept of CALL into the language education. The following is a review based on Beatty’s book which is also highly recommended as for reading by the reviewer.